Evaluation of Microleakage Between Different Post and Core Systems Under Gradual Loading: an In-Vitro Study - Nurul Aqilah Salim; Nor Aidaniza Abdul Muttlib; Rabihah Alawi; Normastura Abd rahman; Zaihan Ariffin (University of Zagreb. School of Dental Medicine, 2018)
Objective: This study aimed to compare the difference in marginal dye penetration between ever-Stick, Parapost XP, Parapost fiber white and control groups under gradual loading. Materials and Methods: Sixty-eight human maxillary permanent incisors were divided into four groups. Each specimen was endodontically treated with step-back technique and prepared for each post system according to experimental groups, subsequently cemented in the canal. Composite resin cores were built and laboratory fabricated metal crowns were cemented. All specimens except those in the control group were subjected to thermal cycling. All groups were subjected to gradual loading from 0N-50N for 100 cycles. Specimens were sectioned transversely and the depths of dye penetration along the post were measured. Data were entered in SPSS ver. 22 and analyzed using two-way ANOVA test. Results: There was no significant difference in marginal dye penetration between each group (p-value>0.05). However, there was a significant difference in percentage of marginal dye penetration between all groups (p-value<0.05); post-hoc comparison showed significant difference between Fiber White and Control groups (p-value=0.009). Conclusion: All the groups showed dye penetration but the percentage was significant only between Parapost Fiber White and the control groups.